Understanding customer orientation behaviour: a study on non-academic staff in UiTM Kuala Terengganu / Syahrul Hezrin Mahmud, Fatimah Zainab Dzulkifli and Najdah Abd Aziz - Mahmud, Syahrul Hezrin; Dzulkifli, Fatimah Zainab; Abd Aziz, Najdah (2011)
The readiness of the staff in term of attitude and behaviour towards customer orientation behaviour is the key factor in delivering quality services and ensuring customer satisfaction. This study stresses on the attitudinal and behavioural aspects of non-academic staffs towards the concept of customer orientation behaviour. This attitudinal and behavioural aspects comprise of four variables; customer orientation behaviour, leadership, organization culture and interpersonal skills. The demographic aspect is also considered as one of the components that contribute towards customer orientation behaviour. The designed questionnaire is organized into five sections according to the variables and demographic factor. The questionnaires are being distributed to 100 non-academic staff. The respondents consisted of six departments at UiTM Kuala Terengganu which included the Administration, Student Affair, Bursary, Academic Affair, Library, and'Facilities Services. Data were collected using the cluster samples method, wherepy the population had been divided into departments/ clusters, then randomly selected some of those and then choose randomly from those selected cluster. Hence the questionnaires given to the respondents were under close supervision of the researchers. This data is then analyzed using SPSS. All of the variables, namely leadership, organization behaviour and interpersonal skills tested significantly to the customer orientation. Interpersonal skill was found to be most influential towards customer orientation behaviour while Library was found'as the best department that cultivated customer orientation behaviour. Based on the findings of this research, the researchers recommend a few mechanisms and initiatives in order to improve customer orientation behaviour. In the near future this research will be extended on researching the relationship between customer orientation behaviour, customer satisfaction, pro-social organizational behaviour (POB), and customer orientation as surface traits (COS) and Organizational Citizenship Behaviour (OCB).